Graphic Medicine in the University - Squier, Susan M. (The Hastings Center report, 2015)
The spring I first offered a graphic medicine graduate seminar, I wasn't sure what to expect. Every class meeting included one hour in which the students, from fields that stress rigorous verbal and written achievement, were required to embrace the position of the amateur by learning to create comics. They experimented with putting images and words together in sequential drawn panels in order to tell a story of their own devising. Of course, they did more than draw; the other two hours of the seminar introduced them both to the medium of comics and to graphic medicine in particular. What happened surprised me. Not only did the students, none of whom were medical students, explore illness, disability, and medical treatment in their comics, but they also often articulated bioethics issues as well.